Corticosteroid and cyclophosphamide in acute exacerbation of idiopathic pulmonary fibrosis: a single center experience and literature review - Novelli, Luca; Ruggiero, Roberto; De Giacomi, Federica; Biffi, Alice; Faverio, Paola; Bilucaglia, Luca; Gamberini, Silvia; Messinesi, Grazia; Pesci, Alberto (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Acute Exacerbation (AEx) is a frequent and severe complication of Idiopathic Pulmonary Fibrosis (IPF). In the absence of consensus regarding treatment, studies evaluating the efficacy of specific therapies, such as corticosteroids and immunosuppresant agents, are needed. In this case series we evaluated the outcome in terms of survival of intravenous pulse doses of high-dose corticosteroid (methylprednisolone 1000 mg per day for 3 consecutive days) followed by montlhy cyclophosphamide administration (maximum 6 doses) in a cohort of patients with AEx-IPF referred to the Respiratory Unit, San Gerardo University Hospital, Monza, Italy, from 2009 to 2013. A total of 11 patients (7 males, median age 65 years) were enrolled. A median of five monthly pulse doses of cyclophosphamide were administered, with four patients receiving all 6 doses. Four patients died before completion. Three patients developed adverse events. Overall survival at 3 months was 73%, at 6 months 63%, at 12 months 55%, at 18 months 45% and at 2 years 27%. In-hospital mortality was 9%. Causes of death were: six respiratory failures from disease progression, one lung cancer and one breast cancer. Two patients received lung transplantation and were excluded from the Kaplan-Meier analysis. In conclusion, combined intravenous pulse doses of high-dose corticosteroid and cyclophosphamide could be a reasonable add-on therapy for AEx-IPF, considering the few side effects and safe profile. A complete and rapid diagnostic work-up associated to the proper management (e.g. support of respiratory failure with non-invasive ventilation) in the right setting, may also have a positive effect on patients’ outcome.